LOS ROLES DE GÉNERO A TRAVÉS DE LA ADAPTACIÓN CINEMATOGRÁFICA DE LA OBRA DE MIGUEL DELIBES. LA PIRÁMIDE DE MASLOW O ¿CUÁNTAS REGULAS HA COSTADO UNA LOLA? - Almudena OJEDA TORRERO (Fonseca, Journal of Communication, 2023)
In this paper we analyze step by step the role of women through the film adaptation of writer Miguel Delibes. For this, and using our eyes or "feminist glasses" combine two types of analysis. The specialist provided by the film and feminism, A. Kuhn, with the proposal of A. Maslow's hierarchy of human needs.